A study the utilization of waste heat from engine to run air conditioning system / Syadilla Aid. - Aid, Syadilla (2009)
Automobile engine generate significant waste heat, which could be recovered and· converted to the useful energy. Most of energy is loss of heat. Since most of the energy consumed by the internal combustion engine is wasted, capturing much of that wasted energy can provide a large increase in efficiency. The possibilities of where and how the lost energy from engine can run the air conditioning system are studied, leading to great improvement and reduction of pollution and gas emissions. In this paper also proposed the design concept of absorption system to store that wasting heat which gives bad effect to our breath.